Impact of prior vaccination on antibody response and influenza-like illness among Australian healthcare workers after influenza vaccination in 2016. Issue 24 (2nd June 2021) - Leung, Vivian K.Y.; Fox, Annette; Carolan, Louise A.; Aban, Malet; Laurie, Karen L.; Druce, Julian; Deng, Yi-Mo; Slavin, Monica A.; Marshall, Caroline; Sullivan, Sheena G.
Highlights: Antibody titres of healthcare workers were compared by prior vaccination history. Healthcare workers in our study demonstrated protective antibody titres post-vaccination. Different antibody responses observed for each influenza vaccine strain. Greater post-vaccination responses observed among vaccine-naïve healthcare workers. Repeated vaccination appears to attenuate NI antibody response to A(H3N2). Abstract: Background: Epidemiological studies suggest that influenza vaccine effectiveness decreases with repeated administration. We examined antibody responses to influenza vaccination among healthcare workers (HCWs) by prior vaccination history and determined the incidence of influenza infection. Methods: HCWs were vaccinated with the 2016 Southern Hemisphere quadrivalent influenza vaccine. Serum samples were collected pre-vaccination, 21–28 days and 7 months post-vaccination. Influenza antibody titres were measured at each time-point using the haemagglutination inhibition (HI) assay. Immunogenicity was compared by prior vaccination history. Results: A total of 157 HCWs completed the study. The majority were frequently vaccinated, with only 5 reporting no prior vaccinations since 2011. Rises in titres for all vaccine strains among vaccine-naïve HCWs were significantly greater than rises observed for HCWs who received between 1 and 5 prior vaccinations (p < 0.001, respectively). Post-vaccination GMTs against influenza A but not B strains decreased as the number of prior vaccinations increased from 1 to 5. There was a significant decline in GMTs post-season for both B lineages. Sixty five (41%) HCWs reported at least one influenza-like illness episode, with 6 (4%) identified as influenza positive. Conclusions: Varying serological responses to influenza vaccination were observed among HCWs by prior vaccination history, with vaccine-naïve HCWs demonstrating greater post-vaccination responses against A(H3N2).